High-relaxivity contrast-enhanced magnetic resonance neuroimaging: a review - Giesel, Frederik L.; Mehndiratta, Amit; Essig, Marco (European radiology, 2010)
Evaluation of brain lesions using magnetic resonance imaging (MRI) provides information that is critical for accurate diagnosis, prognosis, therapeutic intervention and monitoring response. Conventional contrast-enhanced MR neuroimaging using gadolinium (Gd) contrast agents primarily depicts disruption of the blood-brain barrier, demonstrating location and extent of disease, and also the morphological details at the lesion site. However, conventional imaging results do not always accurately predict tumour aggressiveness. Advanced functional MRI techniques such as dynamic contrast-enhanced perfusion-weighted imaging utilise contrast agents to convey physiological information regarding the haemodynamics and neoangiogenic status of the lesion that is often complementary to anatomical information obtained through conventional imaging. Most of the Gd contrast agents available have similar T1 and T2 relaxivities, and thus their contrast-enhancing capabilities are comparable. Exceptions are gadobenate-dimeglumine, Gd-EOB-DTPA, Gadobutrol and gadofosveset, which, owing to their transient-protein-binding capability, possess almost twice (and more) the T1 and T2 relaxivities as other agents at all magnetic field strengths. Numerous comparative studies have demonstrated the advantages of the increased relaxivity in terms of enhanced image contrast, image quality and diagnostic confidence. Here we summarise the benefits of higher relaxivity for the most common neuroimaging applications including MRI, perfusion-weighted imaging and MRA for evaluation of brain tumours, cerebrovascular disease and other CNS lesions.
Gesehen am 15.03.2023